2021
DOI: 10.1111/bph.15350
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin induces p53‐independent cancer cell death through lysosome activation by the transcription factor EB and Reactive Oxygen Species‐dependent ferroptosis

Abstract: Background and Purpose Cancer cells exhibit more dependence on iron and enhanced sensitivity to iron‐dependent, programmed cell death (ferroptosis) than normal cells. Quercetin exerts anti‐cancer effects, but the underlying molecular mechanism is largely unknown. In this study, we aimed to investigate the involvement of lysosome function and ferroptosis in the anti‐cancer potential of quercetin. Experimental Approach We used MTT assays and DNA content analysis to evaluate the cytotoxicity, colony formation ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 46 publications
3
82
0
Order By: Relevance
“…Moreover, senolytics also have other effects. For example, the antioxidant quercetin inhibits ferroptosis and can decrease inflammation and lipid metabolism, all pathways that are associated with NAFLD [81,82]. Although it has been suggested that senolytics could be administrated intermittently, thereby reducing the risks of adverse events, large clinical trials are needed to define the benefits and potential risks of these drugs.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, senolytics also have other effects. For example, the antioxidant quercetin inhibits ferroptosis and can decrease inflammation and lipid metabolism, all pathways that are associated with NAFLD [81,82]. Although it has been suggested that senolytics could be administrated intermittently, thereby reducing the risks of adverse events, large clinical trials are needed to define the benefits and potential risks of these drugs.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…This multi-marker approach enables the detection of senescent cells in various experimental settings and tissues. Promising results have been achieved in the first clinical trials targeting cellular senescence in humans 80 , 81 Therefore, it is of critical importance to develop, implement, test, and harmonise methods and standard operating protocols for translational early phase trials of agents that target fundamental aging processes. New, effective and low-cost assays are needed to detect and trace senescence in blood, cells and biopsies of the targeted organ for use in clinical trials.…”
Section: Markers and Detection Of Cellular Senescencementioning
confidence: 99%
“…The activated lysosome degrades ferritin and then promotes ferroptosis through iron release and subsequent lipid oxidation. [90] Amentoflavone (AF) is a polyphenol which has been widely found in Selaginella. [91] It has attracted increasing interests because of its anti-tumor effects.…”
Section: Nanoparticulate Inducersmentioning
confidence: 99%
“…Ferroptosis is an iron-dependent non-canonical PCD mechanism, driven by the accumulation of lipid peroxides. In hepatocellular carcinoma HepG2 cells, quercetin (50 μM) promoted both apoptosis and ferroptosis [22]. Indeed, lysosome-dependent cell death induced by quercetin was associated with the promotion of ferritin degradation [22], a process known as ferritinophagy, which enhances the cellular free iron content, thus increasing lipid peroxidation and promoting ferroptotic cell death [23].…”
Section: O P Y R I G H T E D R a S P Amentioning
confidence: 99%
“…In hepatocellular carcinoma HepG2 cells, quercetin (50 μM) promoted both apoptosis and ferroptosis [22]. Indeed, lysosome-dependent cell death induced by quercetin was associated with the promotion of ferritin degradation [22], a process known as ferritinophagy, which enhances the cellular free iron content, thus increasing lipid peroxidation and promoting ferroptotic cell death [23]. Necroptosis, instead, relies on the activation of RIPK1 (receptor interacting serine/threonine kinase 1) that leads to the formation of the so-called necrosome complex.…”
Section: O P Y R I G H T E D R a S P Amentioning
confidence: 99%